A Novel Single Phase Soft Switched PFC Converter - Altintas, Nihan (SPRINGER SINGAPORE PTE LTD, 2014)
In this study, a novel single phase soft switched power factor correction (PFC) converter is developed with active snubber cell. The active snubber cell provides boost switch both to turn on with zero voltage transition (ZVT) and to turn off with zero current transition (ZCT). As the switching losses in the proposed converter are too low, L and C size can be reduced by increasing the operating frequency. Also, all the semiconductor devices operate with soft switching. There is no additional voltage stress in the boost switch and diode. The proposed converter has a simple structure, low cost and ease of control as well. It has a simple control loop to achieve near unity power factor with the aid of the UC3854. In this study, detailed steady state analysis of the proposed converter is presented and this theoretical analysis is verified by a prototype of 100 kHz and 500 W converter. The measured power factor and efficiency are 0.99 and 97.9% at full load.
Keywords: Power factor correction; AC-DC converter; Zero current transition; Zero voltage transion; PWM CONVERTERS; Engineering